Bioaksesibilitas Senyawa Fenolik Minuman Kakao Pasteurisasi dengan Penambahan Matriks Susu - Sari, Dwi Indah Permata; Prangdimurti, Endang; Indrasti, Dias (Jurnal Teknologi dan Industri Pangan, 2025)
Cocoa beans and their derivatives are well-known for their health benefits, primarily attributed to phenolic compounds. While some research has explored the interactions of these compounds within food matrices, there were few reports on the release of cocoa phenolics in the gastrointestinal tract when consumed as part of complex foods. This study aimed to evaluate how incorporation of whole-fat milk powder (CF), skimmed milk powder (CS), and whey protein powder (CW) into pasteurized cocoa beverages impacts the in vitro release of phenolic compounds throughout gastrointestinal digestion. The initial analysis included quantifying total phenolics and flavonoids in the undigested samples. Subsequently, simulated gastrointestinal digestion was performed, followed by analysis of total phenolics and flavonoids at each digestion stage. The extent of compound release was expressed as the recovery index (RI) and bioaccessibility index (BI). The results showed that the addition of milk matrices (CF, CS, CW) significantly decreased the total phenolic content of cocoa beverages (p<0.05) across all digestion phases. CW had the highest RI for total phenolics (202.67±7.67%). This study suggests that although the addition of milk decreased the initial phenolic content in undigested cocoa beverages, an increase in RI of phenolics was observed after the gastric digestion phase, especially in the beverages containing whey protein.